(untitled) (Research, Society and Development, 2023)
Introduction: Parkinson’s disease is an chronic neurodegenerative disorder, whose prevalence has become a major public health problem associated with aging. Physical therapy is a treatment modality that is known to improve the functionality of individuals, but there are few studies that evaluate it when applied at home. Objectives: to investigate the effects of a home rehabilitation physical therapy program for patients with Parkinson’s disease. Methods: it’s a therapeutic intervention study, carried out between July and November 2022. This work was approved by the Research Ethics Committee (CEP) of Federal University of Pará (UFPA). 22 participants were evaluated before and after 12 sessions using an evaluation form consisting of anamnesis, physical examination and a composite form Hoehn & Yahr Scale (EH&Y), Time Up and Go Test, Sitting and Standing Test - 5 times , International Physical Activity Questionnaire (IPAQ), Brazilian OARS (BOMFAQ) and Parkinson’s Disease Questionnaire - 39 questions (PDQ-39). Results: 88% of patients were classified in EH&Y as grade I or III. 6 seniors (68% male and 32% female) completed the treatment. The intervention had strong statistical significance on the TUG, TSL and BOMFAQ (p=0.00) and PDQ-39 (p=0.01). There was no statistical stability in the data collected with the IPAQ (p=0.31). Conclusion: In the observed population, the home rehabilitation protocol was effective in improving gait, lower limb strength, performing activities of daily living and quality of life.